Nonimmune thyroid destruction results from transgenic overexpression of an allogeneic major histocompatibility complex class I protein. - Frauman, A G (1993)
The overexpression of major histocompatibility complex (MHC) class I molecules in endocrine epithelial cells is an early feature of autoimmune thyroid disease and insulin-dependent diabetes mellitus, which may reflect a cellular response, e.g., to viruses or toxins. Evidence from a transgenic model in pancreatic beta cells suggests that MHC class I overexpression could play an independent role in endocrine cell destruction. We demonstrate in this study that the transgenic overexpression of an allogeneic MHC class I protein (H-2Kb) linked to the rat thyroglobulin promoter, in H-2Kk mice homozygous for the transgene, leads to thyrocyte atrophy, hypothyroidism, growth retardation, and death. Thyrocyte atrophy occurred in the absence of lymphocytic infiltration. Tolerance to allogeneic class I was revealed by the reduced ability of primed lymphocytes from transgenic mice to lyse H-2Kb target cells in vitro. This nonimmune form of thyrocyte destruction and hypothyroidism recapitulates the beta-cell destruction and diabetes that results from transgenic overexpression of MHC class I molecules in pancreatic beta cells. Thus, we conclude that overexpression of MHC class I molecules may be a general mechanism that directly impairs endocrine epithelial cell viability.